SEA DEFENSE STRATEGY AND URGENCY OF FORMING MARITIME COMMAND CENTER - Lukman Yudho Prakoso; Suhirwan Suhirwan; Kasih Prihantoro (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Adagium Si Vis Pacem Para Bellum, which means who wants peace, prepare for war. Faced with the dynamics of the global and regional strategic environment affecting the defense system that must be prepared by Indonesia. China's aggressive action in the Natuna Sea is one proof that defense in the Indonesian sea is still a serious concern that must be addressed. The aim of this study is to find the best sea defense strategy, to secure the New Capital, especially in the sea area. The study was carried out in the sea area which is the responsibility of the Makassar Navy Base VI. This study uses George Edward III's public policy implementation theory, qualitative descriptive is the method used with the phenomenological approach. The results of this study show that the implementation of the transmission subfactor, communication is only limited to the internal communication of each law enforcement entity, there is no integrated operational-tactical operational nature. The implementation of the communication clarity sub-factor between law enforcement entities is also not yet optimal, due to the limited facilities and other facilities, especially related to the problem of operational-tactical communication equipment. While the implementation of the communication consistency subfactor, the existence of regulations on each entity as the operational basis at sea, makes the bureaucratic procedures ineffective and inefficient. In conclusion, the communication factor between law enforcement entities must be a priority, so that performance can be optimally effective and efficient, integrated hardware, software, and brainware must be built. An entity that can act as the main controller that can coordinate all entities related to law enforcement at sea, and see the results of research related to the entity that has the greatest potential as a controller of sea security in the Makassar region, the researchers recommend the Navy as the Command Center.